Scientific and philosophical theory of sports: real state and development prospects - Mamedov, A. A.; Sherstyuk, M. V.; Zaitsev, A. A.; Gnezdilova, E. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to based on critical analysis, substantiate the development of a philosophical theory of physical culture and sports.